Penerapan Pembelajaran Berdiferensiasi Berdasarkan Gaya Belajar untuk Meningkatkan Kemampuan Berhitung Siswa di Kelas III Sekolah Dasar: Penelitian - Shella Heryani; Rita Novita; Intan Kemala Sari (Jurnal Pustaka Cendekia Pendidikan, 2026)
Mathematics learning in elementary schools still encounters challenges because differences in students' learning characteristics are often not considered when designing instructional strategies. As a result, students' numeracy skills have not developed optimally, highlighting the need for an approach that accommodates diverse learning needs. This study aimed to analyze the effectiveness of differentiated instruction based on learning styles in improving the numeracy skills of third-grade students at SD Negeri 22 Banda Aceh. A quantitative approach employing a One Group Pretest-Posttest Design was used, involving 30 students as research participants. Data were collected through learning style diagnostic tests, classroom observations, pretests, and posttests, and analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Wilcoxon Signed Rank Test. The findings revealed that the auditory learning style was the most dominant, followed by visual and kinesthetic learning styles. The implementation of differentiated instruction improved numeracy performance across all learning-style groups, with the greatest improvement observed among auditory learners. The Wilcoxon test produced an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), indicating a statistically significant difference between pretest and posttest scores. These findings demonstrate that differentiated instruction based on learning styles effectively enhances students' numeracy skills while fostering a more adaptive, meaningful, and student-centered mathematics learning process in elementary education.